2017
DOI: 10.11114/jets.v5i1.2056
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Zero Relative Clauses in English by Adult Turkish Learners of English

Abstract: Studies on acquisition of relative clauses by first and second language learners have evoked considerable interest in recent decades. In line with such studies, in this present study we aim to show the possible effect of first language (Turkish) on second language (English) in zero relative clause constructions. English uses certain stranded prepositions in zero relative clauses, whereas Turkish uses the same suffix in non-subject relative clause constructions. This observation in two typologically different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Housen and Simoens (2016) note that acquisition of relative clause constructions might result from the asymmetry and complexity of these constructions. Ordem (2017) also found that adult Turkish learners of English had difficulty producing certain prepositions in zero relative clause constructions. Wiechmann (2015) also emphasizes that acquisition of object relative clauses may be hard to process.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Housen and Simoens (2016) note that acquisition of relative clause constructions might result from the asymmetry and complexity of these constructions. Ordem (2017) also found that adult Turkish learners of English had difficulty producing certain prepositions in zero relative clause constructions. Wiechmann (2015) also emphasizes that acquisition of object relative clauses may be hard to process.…”
Section: Discussionmentioning
confidence: 88%
“…Studies regarding relative clause have been incremental in Turkish context as well (Boran, 2018;Ordem, 2017;Ordem, Özezen, Darancık, Mavaşoğlu and Hadutoğlu 2018;Ozcelik, 2006;Paluluoğlu, 2017;Turan, 2012Turan, , 2018Yas, 2016). However, there are fewer studies on the production of adjective clauses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations